Cointegration analysis on trading behavior in four SELECTED asean countries BEFORE MONETARY CRISIS - Prawoto, R. Budi (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This paper aims to analyze Indonesian position among the trading behavior in four selected ASEAN countries (according to their import-and-export products) using cointegration analysis. The demands for export and import are estimated before the monetary crisis erupted (1963 â 1995) using the dynamic OLS (DOLS) method. The Johansen Maximum Likelihood (JML) approach is also employed to compare the results obtained. The results show that foreign income has a significant impact on export demand, suggesting that foreign disturbance in the form of economic activities is likely to be transmitted to these countries. The Marshall Lerner conditions are easily met for the cases of Malaysia and Thailand (DOLS and JML). For Indonesia and the Philippines, the sum of the price elasticities of export and import demand are less than unity. This can be explained by the J-curve, in which the currency depreciations will first worsen the trade balance before it improves, and it takes a long time to affect the trade balance.